ANALISIS KISAH TELADAN NABI MUHAMMAD DALAM PEMBENTUKAN KARAKTER KEAGAMAAN SISWA DALAM PEMBELAJARAN SKI MI - Khilma Amil Diana; Naili Muna Azizah; Zanuba As’ada; Naula Salsabila; Qurrotul Uyun; Naelatus Sifa; Hasfa Razaq; Dian Rif’iyati (STKIP Subang, 2026)
This study aims to analyze the role of the exemplary stories of the Prophet Muhammad (peace be upon him) in shaping students’ religious character in Islamic Cultural History (SKI) classes at elementary madrasahs, particularly in influencing students’ religious attitudes, values, and behavior in their daily lives. This study employs a descriptive qualitative approach using library research. Data were obtained from various sources, including books, scientific journals, articles, and relevant documents. Data collection involved documentation, while data analysis was conducted through data reduction, data presentation, and the systematic drawing of conclusions. Research findings indicate that the exemplary stories of the Prophet Muhammad (peace be upon him) in Islamic Cultural History (SKI) education play a role in shaping the religious character of students in Islamic elementary schools. Students become more active and find it easier to understand the material. The stories of the Prophet Muhammad (peace be upon him) serve not merely as subject matter, but as a means of instilling religious and moral values in students. The novelty of this study lies in its specific focus on analyzing the role of exemplary stories about the Prophet Muhammad (peace be upon him) in the context of Islamic Studies (SKI) instruction at elementary madrasahs, a topic that has yet to be thoroughly explored. This study also integrates various sources of literature to underscore the relevance of these exemplary stories as a strategy for fostering students’ religious character.